2018
DOI: 10.1016/j.bpj.2018.03.019
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between α-Helical Conformation and Amyloidogenicity

Abstract: Amyloid fibrils are stable aggregates of misfolded proteins and polypeptides that are insoluble and resistant to protease activity. Abnormal formation of amyloid fibrils in vivo may lead to neurodegenerative disorders and other systemic amyloidosis, such as Alzheimer's, Parkinson's, and atherosclerosis. Because of their clinical importance, amyloids are under intense scientific research. It is believed that short polypeptide segments within proteins are responsible for the transformation of correctly folded pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Positive (Pα-Pc) values (Figure 2B, left panel) indicated high α-helix propensities in theory, and indeed the N-terminal region with positive (Pα-Pc) values maintained a helix in the MD simulation of a native αSyn (PDB ID: 2kkw [64]), even in the absence of micelles (Figure 2D). The β-sheet in the region 89-95 with positive-(Pα-Pc) values (Figure 2B) yielded a similar contribution of high α-helix propensities to amyloid formation as reported in the literature, which explains why amyloidogenic proteins often have α-helices in native conformations, e.g., Aβ and PrP [65,66,67,68]. Given the correlation of the predicted propensity profiles with the structures of αSyn amyloid in silico, next, we introduced substitution mutations of isoleucine around the three loops encompassing residues 56–62 [loop(56–62)], 67–68 [loop(67–68)], and 84–87 [loop(84–87)] (Figure 2A), specifically Glu61Ile (E61l), Asn65Ile (N65I), and Gly84Ile (G84I), respectively (Figure 3A,B).…”
Section: Insights From MD Simulations Of αSyn Amyloidssupporting
confidence: 77%
“…Positive (Pα-Pc) values (Figure 2B, left panel) indicated high α-helix propensities in theory, and indeed the N-terminal region with positive (Pα-Pc) values maintained a helix in the MD simulation of a native αSyn (PDB ID: 2kkw [64]), even in the absence of micelles (Figure 2D). The β-sheet in the region 89-95 with positive-(Pα-Pc) values (Figure 2B) yielded a similar contribution of high α-helix propensities to amyloid formation as reported in the literature, which explains why amyloidogenic proteins often have α-helices in native conformations, e.g., Aβ and PrP [65,66,67,68]. Given the correlation of the predicted propensity profiles with the structures of αSyn amyloid in silico, next, we introduced substitution mutations of isoleucine around the three loops encompassing residues 56–62 [loop(56–62)], 67–68 [loop(67–68)], and 84–87 [loop(84–87)] (Figure 2A), specifically Glu61Ile (E61l), Asn65Ile (N65I), and Gly84Ile (G84I), respectively (Figure 3A,B).…”
Section: Insights From MD Simulations Of αSyn Amyloidssupporting
confidence: 77%
“…Earlier studies have shown that the α-helix to β-sheet transition plays a key role in the mechanism of amyloid formation. , To investigate the effects of boron nitride (BN) nanoparticles on the conformational transition of Aβ(1–42), we have calculated the time evolution of the secondary structure of each residue of the peptide in the presence of nanoparticles of different curvatures and compared the results with those in the absence of any nanoparticle (Figure ). In the absence of any nanoparticle, the initial secondary structure of the peptide is significantly modified after equilibration in water, which is shown in Figure a.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although the mechanism of amyloid formation is not yet fully resolved, , various experimental studies have proposed that the initial random coil or α-helical structure of Aβ(1–42) monomers first get converted to β-sheet structures which then assemble to form Aβ aggregates. There are many studies which have shown that the generation of β-sheet conformations favors amyloid fibrillization. The α-helix to β-sheet transition is believed to play a major role in amyloid assembly. ,, Hence, the primary aim of a large number of existing studies has been to avert the random coil or helix to β-sheet transitions of Aβ monomers to prevent amyloid formation. , , The Aβ aggregation process can be prevented in two ways: First, if the initial helical structure of the peptide is stabilized by some external material or condition, that would stop or delay the helix to β-sheet transition, which means that the peptide should be trapped in the initial nonamyloi­dogenic conformation. ,− Next, if interactions with an external material can destroy or break the prefibrillar conformations of the Aβ peptide and convert them into random coil conformations, , then that would also prevent the formation of β sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the proposed mechanism for the Aβ aggregation process involves mainly the steps: Random coil (RC) → α-structure → β-structure → Aβ-aggregates. The helix to β-strand transition plays an important role in the aggregation process. Hence, to prevent β-sheet structure formation, one can start either by taking directly the prefibrillar structures and destroying them by using some carbonaceous materials that convert them to RC or by stabilizing the helical intermediate so that it is trapped in an energy well of non-amyloid conformation and blocks and/or delays the fibril formation process. ,− Recent studies showed that the trimer and tetramer species of Aβ(1–42) are the most neurocytotoxic forms of low-molecular weight (LMW) oligomers that bind with the neurons causing the cell deaths. Experimentally, we have only limited structural information about the Aβ(1–42) trimer because of its transient nature. ,, The goal of this study is to find ways of preventing the Aβ-trimerization process and their fibril formation. Earlier experimental and theoretical studies have looked for short peptides/proteins, small organic molecules (natural as well as synthetic), antibodies, and nanoparticles , for the treatment of AD.…”
Section: Introductionmentioning
confidence: 99%